Uji Akurasi Arah Kiblat Masjid Laju Sumenep - Anaam, Khairul; Ilmiyah, Ma'rifatul; Saajid, Muhammad Zaidan (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
The Sumenep Laju Mosque was built in 1639 AD during the reign of Raden Ario Anggadipa as the XXI King of Sumenep (1626M – 1644M), exactly 5 years before his reign ended. Departing from the background of the construction of the Speed ??Mosque which is already 384 years old. Therefore, the authors are interested in conducting research to test the accuracy of the Qibla direction at the Sumenep Sumenep Mosque. The results showed that the Qibla direction accuracy test at the Sumenep Speed ??Mosque using the sun's shadow method at any time has a deviation from the Qibla azimuth value which should be 8° 31' 51" less to the north. While the Qibla direction accuracy test at the Sumenep Sumenep Mosque using Google Earth has a deviance of 8° 22' 12" less to the north than the proper Qibla azimuth value.